Determinants of CSR disclosure quality : An Empirical study on Moroccan banking sector - HAFIDI ALAOUI , Moulay Smail; BOURAS , Hajar (Revue Internationale des Sciences de Gestion, 2025)
This paper endeavor to investigate the potential impact of CG mechanism on CSR disclosure quality in an emerging country, Morocco. This study examines 36 CSR reports of 9 Moroccan listed banks from 2020 to 2023 using content and multiple regression analysis, based on GRI index to measure CSR disclosure quality. Evidence shows that board characteristics (board size and board independence) typically linked to the protection of stockholder' profits, are positively correlated with the quality of CSR reports. This suggests that, in the context of CSR reporting, larger and more independent boards effectively promote both stockholder and stakeholder interests. Gender diversity, particularly a higher proportion of female directors, also positively influences the quality of CSR disclosure. This may be due to women's greater sensitivity to societal needs, leading to more socially conscious boards, which in turn develop more effective CSR strategies. Surprisingly, the presence of a female CEO or chairperson does not appear to affect CSR disclosure quality. However, the existence of a CSR council has a positive impact on CSR reporting, with such committees being associated to a greater propensity to disclose ESG information.